The Role of Leadership Styles in Employee Engagement and Retention - Nurjanah, Iva; Octafian, Ray (Journal of Economics, Management, Accounting and Computer Applications, 2025)
The purpose of this study is to explore the influence of leadership styles on engagement and retention within an organization, using a case study of the Glawan Village Government, Pabelan Subdistrict, Semarang Regency. Employing a qualitative research approach, semi-structured interviews were conducted with 15 to 20 individuals in the Glawan Village Government to gain insights into their experiences and perspectives on leadership practices. Participants were selected using purposive sampling to ensure they had substantial experience with leadership and engagement. Data were analyzed through thematic analysis, which helped identify key themes and patterns related to the effects of leadership on engagement and retention in the Glawan Village Government. Findings reveal that transformational and servant leadership styles significantly positively impact engagement and retention in the Glawan Village Government. Individuals under such leaders reported higher levels of motivation, job satisfaction, and loyalty. In contrast, transactional leadership was found to have a more limited effect on engagement, as it primarily focuses on task completion and performance rewards without fostering deeper emotional connections. Those working under transformational and servant leaders in the Glawan Village Government described feeling valued, supported, and connected to the organization, leading to higher engagement and stronger intentions to remain with the organization. This study highlights the importance of adaptive leadership practices that meet the evolving expectations of a diverse workforce in the Glawan Village Government, particularly in promoting a positive work culture and providing opportunities for personal development. These insights contribute to academic research and practical recommendations for the Glawan Village Government in their efforts to enhance engagement and reduce turnover through effective leadership.